Design and Stress Simulation of Crankshaft for Slider Crank-Drive Stirling Engine - Mohd Farid, Zainudin; R. A., Bakar; Gan, Leong Ming; Tanti Zanariah, Shamshir Ali; Billy, Anak Sup (Trans Tech Publications, 2015)
In this present work, the design and simulation of crankshaft for multi-cylinder Stirling engine is studied based on finite element analysis. The proposed crankshaft design is based on the typical crosshead slider-crank mechanism that is being used with the consideration of design needs for multi-cylinder Stirling engine. The study focused on the piston-crankshaft assembly that is subjected to compression load in Stirling cycle. Based on the simulation results, the maximum von Mises stress for crankshaft model varies from 0.82 MPa at 1 bar charge pressure to 1.65 MPa at 20 bar charge pressure. Minimum factor of safety is founded to be 33 with maximum deformation under maximum charge pressure. For piston-crankshaft assembly load, minimum factor safety of 2 was observed with maximum compression pressure for minimum charge pressure. The results indicate no yielding and structural failure under compression load case, can be satisfied.